Chemical composition and formula of apatites from theTrês Estradas Carbonatite - Henrique De Maman Anzolin (PANGAEA, 2018)
These tables shows the results obtained by electron microprope analysis of apatites from the Três Estradas Carbonatite. The four types of apatite identified associated with the carbonatite were analysed using a Cameca ®SXfive equipment to determine the chemistry of different types of apatite, whose results are arranged in the table Electron Microprope Results. The data was used to calculate the chemical formula, showed in the table Chemical Formula. The CO3 value showed in the median calculated of chemical formula was obtained from micro-raman spectroscopy. The data in the table Electron Microprobe Results is arranged in % units, and the Chemical Formula is in # of ions, calculated on the basis of 26 oxigen.